South–South Student Mobility Research: Mapping Trends, Thematic Directions, and Emerging Gaps - Fadhli, Rahmat; Wang, Guanyu (Jurnal Akuntabilitas Manajemen Pendidikan, 2025)
South–South student mobility has emerged as a significant yet underexplored phenomenon within international education. This study examines the development of South–South mobility research by analysing publication trends, thematic emphases, and research gaps. Drawing on a Bibliometric–Systematic Literature Review (B-SLR) approach, a systematic mapping of 81 empirical studies was conducted, combining descriptive analysis, bibliometric visualization, and thematic clustering techniques. The findings reveal that research remains geographically concentrated on Africa–Asia and Asia–Asia flows, with China, Malaysia, and South Africa serving as dominant destinations. However, newer host countries such as Indonesia and Vietnam are gradually entering the landscape, suggesting emerging shifts in mobility patterns. Thematically, existing scholarship is heavily oriented toward structural factors such as affordability and institutional reputation, while more recent studies begin to explore students’ digital journeys and experiences of transnational belonging. Methodologically, qualitative approaches dominate, although there is a growing need for longitudinal and mixed methods designs to capture the dynamic trajectories of student mobility over time. Significant silences persist, including the underrepresentation of intra-Latin American mobility and limited attention to digital environments shaping students' experiences. The study argues for future research that expands regional coverage, embraces more diverse methodologies, and moves beyond Global North-centric frameworks. By doing so, South–South mobility scholarship can better reflect the complexity and evolving realities of student movements within and across Global South contexts.